Architektoniczne środki tworzenia granic społecznych wokół imigrantów w miastach - Amiri, Oskar (Człowiek i Społeczeństwo, 2014)
Immigrants in the cities sometimes use architectural means to mark their presence, as well as a separate identity. These activities are often superficial, aesthetic, due to the asymmetry in the means of power in the urban space. On the other side there are the planners, having other plans towards enclaves, and the possibility to introduce them. Urban development is therefore a conflict of interest of different groups, and the result illustrates this dispute. It is a dispute which has a different outcome every time, just as the cultures coexisting in the cities are different, with different needs, identities and history.